Determinação de pesticidas organoclorados e fármacos em matrizes ambientais utilizando QuEChERS, extração líquido-líquido (LLE) e extração em fase sólida (SPE) - Schio, Natalí da Silva (2021)
The presence of xenobiotic organic contaminants in water bodies, where arrive from releases of treated or untreated effluent, has raised concerns about impacts related to the richness and biodiversity of aquatic life and human health. Considering the possibility of the increasing presence, persistence, and pseudo-persistence of pesticide and drugs in the environment and possible deleterious effect resulting from it, the objective of this work was to develop and to validate a multi-residue method using QuEChERS and Liquid-Liquid Extraction (LLE), for determination of organochlorine compounds (Aldrin, heptachlor, heptachlor epoxide, endosulfan (α and β), endosulfan sulfate, 4,4'-DEE, dieldrim, endrin, 4,4'-DDD, 4,4'-DDT, endrin aldehyde, Methoxychlor and hexachlorocyclohexane (α-BHC, β-BHC, γ-BHC e δ-BHC)) in soil, sediment, and freshwater, with gas chromatography-tandem electron capture detector (GC/ECD) and Solid Phase Extraction (SPE) for drugs quantification (Carbamazepine, Atenolol, Propranolol, CBZ-DiOH, Caffeine, Naproxen, Ibuprofen, 2-Hydroxycarbamazepine, Estrone, 17-β-estradiol, 17-α-ethinylestradiol, Paracetamol, 2-Hydroxy-ibuprofen and Diclofenac) in freshwater using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), in the collected sample in the regions of Hydrographic Sub-Basin of Ribeirão do Feijão and Hydrographic Sub-Basin of Rio Quilombo, in São Carlos, SP. The proposed method for organochlorine compounds determination was valid for all matrices. For solid samples, the analyte recoveries (%Rec) were between 50% and 117%, with a coefficient of variation (%CV) below 19 and linear correlation coefficient (R2) greater than 0.98, for all analytes. The value of matrix effect (ME) was between -8.73% for α-BHC and 585.35% for endrin. The limit of detection (LOD) was 0.759 µg Kg-1 for 4,4’-DDD and 2.144 µg Kg-1 for endosulfan sulfate, and the limit of quantification (LOQ) was between 2.528 µg Kg-1 and 7.147 µg Kg-1 , for the same analytes. The %Rec was between 40% and 144% for the freshwater sample, with %CV below 24 for 16 analytes analyzed. All R2 was greater than 0.99. The LOD ranged from 1.641 ng L-1 for α-BHC to 4.433 ng L-1 for endosulfan sulfate, while the LOQ was 5.473 ng L-1 and 14.779 ng L-1 for the same analytes. The ME was -13.73% for α-BHC and 393.43% for endrin. Regarding the determination of drugs in freshwater, the %Rec ranges from 93% to 120%, with %CV below ten and R2 greater than 0.98 for all analytes. The values of LOD ranged from 2.885 ng L-1 for ibuprofen to 5.293 ng L-1 for 17-β-estradiol, while the values of LOQ ranged from 9.618 ng L-1 to 17.642 ng L-1, for the same analytes. Regarding collected samples, the analysis performed to the determination of organochlorine compounds showed results below LOD. This was observed for the three matrices in all collect performed. In the analysis for drugs determination, the presence of ten analytes was observed. The caffeine was in all analyzed samples, with concentrations 105.2, 54.9, 52.3, and 184.4 ng L-1. The other analytes determined were atenolol (52.8, 28.3 and 17.2 ng L-1), carbamazepine (22.8, 17.6 and 36.2 ng L-1), propranolol (28.5, 63.9 and 78.4 ng L-1), ibuprofen (53.9 and 10.9 ng L-1), diclofenac (13.4, 42.7 and 22.0 ng L-1). This work contributes to the elaboration of an important scenario of water quality of surface water source of the city São Carlos, which can support public policies for the preservation of the quality of the environment and human health through the development of public policies that inhibit economically predatory initiatives that are harmful to the environment.